Digging in the significance of the internet for the ICT access, uses and desires of women in ICT - Núria VERGÉS BOSCH; Alex HACHE; Eva CRUELLS LOPEZ (Ediciones Universidad de Salamanca, 2011)
Since the 90's the feminist theories of technology have experienced a renewed optimism with the rise of ICT and the development of the third-wave feminisms. However, Research on gender and technology still focuses on studying the exclusion of women from ICT. Conversely, women's experiences and their strategies leading to their inclusion in ICT has received less attention. Motivated by our previous experience in technoactivism and the observation of a remarkable presence of women, within the Donestech Collective, we initiated a research project on the access, uses and desires of women who were involved in technology. Following a cyberfeminist activist research approach we collected, analysed and made visible the experiences and opinions of women in ICT. Our findings suggest a great diversity of women trajectories to ICT as well as heterogeneous technological practices among them where Internet plays a significant role. Moreover, our results show that women in ICT are curious and enthusiastic, want to be empowered, are willing to share the knowledge gained with others, distrust and dislike power relations existing in the technological environments and try to maintain a critical and creative attitude towards technology.